Hubungan Luas Ventilasi dan Pencahayaan Alami Rumah terhadap Tingkat Kepositifan Sputum BTA pada Penderita TB Paru di Puskesmas Tlogosadang - M. Thoriq Satria Dinata; Muhammad Subkhan; Musa Ghufron (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2020)
The Relationship between Ventilation Area and Natural Lighting of the House on AFB Sputum Positive Rate in Patients with Pulmonary TB at Tlogosadang Health Center Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Indonesia is ranked third in the world, contributing 8% of TB cases. The phenomenon that occurs in the working area of the Tlogosadang Health Center is an increase of positive smear TB cases. This is thought to be due to the physical condition of the patient's house with pulmonary tuberculosis, especially the area of ventilation and natural lighting which is not standardized.Objective: To analyze the correlation between the area of ventilation and natural lighting of the house to the level of ARB sputum positivity in patients with pulmonary tuberculosis at Tlogosadang Health Center.Methods: This study used a retrospective cohort design. Research respondents were taken by simple random sampling method on 38 patients with smear-positive pulmonary TB in 2016-2018. Observation of ventilation area (minimum 10% of floor area), while natural lighting (minimum 60 lux). Observation of medical records on the level of ARB positivity (Scanty, +1, +2, and +3) was carried out at the Tlogosadang Health Center Laboratory, then recorded in the observation checklist.Results: The re were 3 respondents with scanty ARB, 20 respondents (+1), 14 respondents (+2), and 1 respondent (+3). More than 65% of the house's natural lighting and ventilation area is not standardized. The results of the analysis of the contingency coefficient test showed the correlation between the area of ventilation (p = 0.60) and natural lighting (p = 0.24) on the level of ARB sputum positivity.Conclusion: There is no correlation between the area of ventilation and natural lighting of the house on the level of ARB sputum positivity in patients with pulmonary tuberculosis at Tlogosadang Health Center. Latar Belakang: Tuberkulosis (TB) adalah penyakit menular yang disebabkan oleh Mycobacterium tuberculosis. Indonesia di peringkat ketiga di dunia menyumbang 8% untuk kasus TB. Fenomena yang terjadi di wilayah kerja Puskesmas Tlogosadang yaitu adanya peningkatan kasus TB BTA positif. Hal ini diduga disebabkan oleh faktor kondisi fisik rumah pasien TB paru khususnya luas ventilasi dan pencahayaan alaminya yang tidak terstandar.Tujuan: Menganalisis hubungan luas ventilasi dan pencahayaan alami rumah terhadap tingkat kepositifan sputum BTA pada penderita TB paru di Puskesmas Tlogosadang.Metode: Penelitian ini menggunakan desain kohort retrospektif. Responden penelitian diambil dengan metode simple random sampling pada 38 penderita TB paru BTA positif pada tahun 2016 - 2018. Pengamatan luas ventilasi (minimal 10% dari luas lantai), sedangkan pencahayaan alami (minimal 60 lux). Pengamatan rekam medis tingkat kepositifan BTA (Scanty, +1, +2, dan +3) dilakukan di Laboratorium Puskesmas Tlogosadang, kemudian dicatat dalam check list observasi.Hasil: Didapatkan 3 responden dengan BTA scanty, 20 responden (+1), 14 responden (+2), dan 1 responden (+3). Lebih dari 65 % luas ventilasi dan pencahayaan alami rumah tidak terstandar. Hasil analisis uji koefisien kontingensi menunjukkan hubungan luas ventilasi (p = 0,60) dan pencahayaan alami (p = 0,24) terhadap tingkat kepositifan sputum BTA.Kesimpulan: Tidak terdapat hubungan luas ventilasi dan pencahayaan alami rumah terhadap tingkat kepositifan sputum BTA pada penderita TB paru di Puskesmas Tlogosadang.